ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA INDUSTRI TRANSPORTATION SERVICES DI BURSA EFEK INDONESIA TAHUN 2009-2012 - Syamsurijal Tan; Agus Syarif (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2014)
This study is conducted to examine the effect of Current Ratio (CR), Debt ToEquity Ratio (DER), Total Asset Turnover (TATO), Return On Equity (ROE) and Earning per Share (EPS) toward stock price on industry Transportation Services that is listed on the Indonesian Stock Exchange from 2009 to 2012. Sampling technique used is purposive sampling.Â The number of samples obtained is as 15 companies from 22 listed companies.Method analysis used isMultiple Linear Regression analysis, hypothesis test using f-statistic to examine the mean of mutual, t-statistic to examine partial and test the coefficient of determination. According to statistical result it is found that the effecr of CR, DER, TATO, ROE, and EPS is significan toward stock price. Otherwise, partially variable that have significat effect is DER, TATO, and ROE. Keywords: Current Ratio (CR), Debt To Equity Ratio (DER), Total Asset Turnover (TATO), Return On Equity (ROE), Earning per Share (EPS) and stock price